Adult experts' perceptions of telemental health for youth: A Delphi study. Issue 1 (20th April 2018) - Howard, Abigail; Flanagan, Mindy; Drouin, Michelle; Carpenter, Maria; Chen, Elizabeth M; Duchovic, Catherine; Toscos, Tammy
Abstract: Objectives: Our objectives were to measure experts' opinions and develop consensus via the Delphi process on the barriers, applications, and concerns associated with telemental health (TMH) for youth. Materials and methods: We delivered 3 online surveys over 2 months in Summer, 2016–2025 adult experts, including adults who experienced youth depression or suicidality, parents of youth with lived experience, and professionals (ie youth mental health researchers, clinicians/staff, or educators). We used the Delphi method to construct Likert and open-ended questions, developing expert consensus over 3 iterative surveys on the barriers and benefits of TMH for youth. Results: Adult experts identified stigma and knowledge barriers to youth mental health care. Although TMH is perceived as beneficial for screening, education, follow-up, and emotional support, no single delivery method (eg websites or instant messaging) was deemed universally beneficial. Discussion: Adults are the developers, administrators, and gatekeepers of youth mental health care. Although adult experts see potential for TMH to supplement traditional therapy via familiar technologies, there is no consensus on the technologies by which TMH should be delivered. However, there is consensus that family members and friends provide potential pathways to care; thus, an online TMH toolkit for youth would be beneficial for both caretakers and practitioners. Conclusion: Telemental health may not overcome barriers for crisis management but adult experts agreed that TMH had potential benefits for youth. Health care organizations should conduct research and provide training and education to youth caretakers and practitioners on potential barriers and benefits of TMH technologies for youth.